2018
DOI: 10.1089/wound.2018.0788
|View full text |Cite
|
Sign up to set email alerts
|

Use of a National Electronic Health Record Network to Describe Characteristics and Healing Patterns of Sickle Cell Ulcers

Abstract: Sickle cell ulcers affect as many as 15% of patients with sickle cell disease in the United States and severely impact quality of life. An understanding of baseline healing patterns is important to inform study design for future trials that test therapies for this disease. In this study, an electronic wound management system was leveraged to analyze retrospective data on 133 unique sickle cell patients who were treated across 114 wound healing centers, and to describe their characteristics and healing patterns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A gestão eletrônica dos registros de saúde obtidos a partir das inspeções regulares das feridas permite avaliar a eficácia dos cuidados prescritos, acompanhar os resultados do tratamento, sinalizar situações de risco, identificar potenciais de infecção e analisar os indicadores de qualidade (Flattau et al, 2018). Portanto, otimiza o tempo da equipe, aprimora a qualidade da assistência, auxilia os gestores nas tomadas de decisão e redução de custos.…”
Section: Discussionunclassified
“…A gestão eletrônica dos registros de saúde obtidos a partir das inspeções regulares das feridas permite avaliar a eficácia dos cuidados prescritos, acompanhar os resultados do tratamento, sinalizar situações de risco, identificar potenciais de infecção e analisar os indicadores de qualidade (Flattau et al, 2018). Portanto, otimiza o tempo da equipe, aprimora a qualidade da assistência, auxilia os gestores nas tomadas de decisão e redução de custos.…”
Section: Discussionunclassified
“…[37][38][39] For example, in leg ulcers, which is a rare but significant complication of SCD, studies have shown that presenting 60 to 90 days from initial occurrence has a negative influence on healing rates. 40 An additional example includes delayed diagnosis of priapism and therapy, which can result in impotence. 41 In the ED, mortality and morbidity outcomes are often a concern with delayed presentation.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment of this orphan disease requires expertise in its pathophysiology, 4 clinical course, and treatment options. However, clinicians who treat adult patients with SCD often lack experience in SCD management, 5 and most wound healing specialists see few patients with sickle cell ulcers 6 . The unique pathophysiology and clinical presentation of sickle cell ulcers merit specific study, and effective management will likely require the development of targeted treatments.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinicians who treat adult patients with SCD often lack experience in SCD management, 5 and most wound healing specialists see few patients with sickle cell ulcers. 6 The unique pathophysiology and clinical presentation of sickle cell ulcers merit specific study, and effective management will likely require the development of targeted treatments. However, as is typical with rare diseases, 7 a paucity of sites with significant concentrations of patients with sickle cell ulcers impedes scientific study.…”
Section: Introductionmentioning
confidence: 99%